Creative ideas generation and personality: evidence from process communication model - Lefebvre, Sixtine; Camarda, Anaëlle (Frontiers in Psychology, 2024)
The present study investigated the relation between personality and ideas generation abilities. Ideas generation was assessed by the "egg task" in which participants had to generate as many solutions as possible to design ways to drop a hen's egg from a height of 10 m so that it does not break. The 102 participants were also presented with the standard Process Communication Model (PCM) questionnaire. Results suggest that idea generation varied according to PCM Base Type of participants. Even if five out of six Base Types (Thinker, Persister, Harmonizer, Promoter and Rebel) presented similar fluency and categorical flexibility, Imaginer Base presented higher scores than other Base Types. These results, discussed according to cognitive control abilities, reinforce the view that PCM can highlight an individual's creative performance considering interindividual differences.